2018
DOI: 10.1111/tri.13310
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor controls immunoregulatory properties of myeloid cells in mouse cardiac allografts - an experimental study

Abstract: Hypoxia-inducible factors (HIFs) play a critical role in inflammatory properties of myeloid-derived cells. The effect of HIFs on myeloid-derived cell functions in organ transplantation remains unknown, however. We transplanted hearts into transgenic mice with myeloid cell-targeted deletions of HIF-1α or its negative regulator von Hippel-Lindau (VHL) to investigate the effects of HIF-1α inactivation or HIF pathway activation, respectively, on ischemia-reperfusion injury (IRI) and acute rejection. Deletion of VH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…The presence of chemokines or chemokine-producing immune cells can however increase the expression of IDO1 under hypoxia (54, 56). Other studies have also reported the upregulation of IDO1 expression upon hypoxic exposure or HIF1α stabilization in neural and immune cells (5759). Taken together, these studies indicate that the regulation of IDO1 under hypoxic conditions is highly cell type specific and also depends upon microenvironmental factors such as immune cell infiltration.…”
Section: Discussionmentioning
confidence: 87%
“…The presence of chemokines or chemokine-producing immune cells can however increase the expression of IDO1 under hypoxia (54, 56). Other studies have also reported the upregulation of IDO1 expression upon hypoxic exposure or HIF1α stabilization in neural and immune cells (5759). Taken together, these studies indicate that the regulation of IDO1 under hypoxic conditions is highly cell type specific and also depends upon microenvironmental factors such as immune cell infiltration.…”
Section: Discussionmentioning
confidence: 87%
“…Under tumor conditions however, hypoxia and HIF-1α seem to drive the development and function of immunosuppressive myeloid cells like TAMs and MDSCs (23, 60, 61). Correspondingly, a recent study showed that overexpression of HIF-1α in myeloid cells leads to diminished transplant rejection and induction of a regulatory phenotype in myeloid cells in a model of heart transplantation (62). To our knowledge, our study is the first describing an impact of myeloid HIF-1α-expression on pregnancy outcome.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, myeloid‐derived suppressor cells reduced T‐cell proliferation. Ultimately, HIF signaling reduced acute rejection and ischemia‐reperfusion injury leading to prolonged allograft survival 185 …”
Section: Hif‐controlled Myeloid Cell Functions—lessons From Animal Experimentsmentioning
confidence: 99%
“…Ultimately, HIF signaling reduced acute rejection and ischemia-reperfusion injury leading to prolonged allograft survival. 185 Synovial tissue from rheumatoid arthritis patients 161,186 and experimental arthritis mice 5 both up-regulated HIFs and myeloid-specific HIF-1𝛼 and HIF-2𝛼 gene deficiency alleviated inflammation in a murine rheumatoid arthritis model. 7,186 Neutrophils isolated from rheumatoid arthritis patients showed enhanced PHD2 and PHD3 mRNA expression in line with induction of proinflammatory HIF target genes.…”
Section: Hif-1𝜶 Improves Myeloid Cell Functions In Infectious and Noninfectious Inflammation Modelsmentioning
confidence: 99%